The Effectiveness of Learning and Innovation Skills (Communication and collaboration) in Enhancing the Oral Competence of Algerian EFL Learners - azil, mohamed; ghawar, omer (Journal of Social Sciences and Humanities, 2021)
This article aims at investigating the effectiveness of integrating learning and innovation skills (communication and collaboration) in EFL oral expression sessions. Learning and innovation skills are being recognised as the skills that separate students who are prepared for increasingly complex life and work environments in the 21st century and those who are not. The study was carried out at Barika University center, in the academic year 2017/2018, where forty first-year students at the department of English experienced communication and collaboration as the main skills when dealing with oral tasks, applying different active learning strategies to overcome the obstacles they face in speaking English.The researcher conducted the study in the form of classroom action research in which he reflected on the strategies and speaking tasks students carried out in class. The obtained results with the help of questionnaires evidenced how students were positively influenced by the learning and innovation skills to an extent that students could transform learning opportunities to participation in lively conversations, expression of opinions and ideas, presentation of information and evaluation of each others’ point of view. Therefore, the researcher deems the integration of learning and innovation skills necessary to improve the oral competence of EFL learners